The Effect Of Green Tourism Marketing On Green Trust To Increase Green Purchase Intention Ecotourism Destination Study - Kharisma Azmi Yoningsih; Andy Mulyana (UNIVED Press, 2025)
Tourism is a rapidly growing sector of the global economy. The tourism sector contributes significantly to a nation's foreign exchange earnings. On the other hand, the development of the tourism sector has both positive and negative impacts on culture, socio-cultural life, and demographic conditions. This study focuses on green tourism marketing, green trust, and green purchase intention, particularly for ecotourism destinations. The research is located in Greater Bandung, specifically at Taman Hutan Raya Ir. H. Djuanda in Bandung Regency, chosen because Greater Bandung recorded a high number of domestic tourist visits, totaling 6.8 million in 2022. Therefore, the research aims to analyze (1) the effect of green tourism marketing on green trust, (2) the effect of green tourism marketing on green purchase intention, (3) the effect of green trust on green purchase intention, and (4) the effect of green tourism marketing on green purchase intention through green trust. The research method is quantitative, with data collected through questionnaires from a sample of 130 people. Data analysis was conducted using the SmartPLS 4.0 application. The results indicate that (1) green tourism marketing significantly affects green trust, (2) green tourism marketing significantly affects green purchase intention, (3) green trust significantly affects green purchase intention, and (4) green tourism marketing significantly affects green purchase intention through green trust.